2001
DOI: 10.1023/a:1009036128275
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: A chromel-alumel thermocouple has been found to catalyse the methane/oxygen reaction, the main products being CO, H 2 with some CO 2 and H 2 O. Regular oscillations in both reactants, products and temperature have been observed at temperatures around 700 • C. Similar behaviour has been obtained using nickel wires.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…Such oscillations have been observed over palladium catalysts [1][2][3][4], and supported nickel catalysts [5][6][7]. It has been observed in our earlier study that chromel/alumel thermocouple wires and nickels wires can also catalyse the methane/oxygen reaction and result in rate oscillations [8].…”
Section: Introductionsupporting
confidence: 54%
“…Such oscillations have been observed over palladium catalysts [1][2][3][4], and supported nickel catalysts [5][6][7]. It has been observed in our earlier study that chromel/alumel thermocouple wires and nickels wires can also catalyse the methane/oxygen reaction and result in rate oscillations [8].…”
Section: Introductionsupporting
confidence: 54%
“…Our previous studies showed that chromel-alumel thermocouples, when no other catalyst was present, can act as effective catalysts for the methane/oxygen reaction oscillating at temperatures between 700 and 740 • C, where nickel was found to be the active ingredient [11]. In this paper we report the first observation of oscillations over cobalt wire/foil metal catalysts when an argon/methane/oxygen mixture was passed and the further investigations into the oscillatory reaction kinetics.…”
Section: Introductionmentioning
confidence: 71%
“…These oscillations can be distinguished from those occurring on the chromel-alumel thermocouple wires because they generally occurred in a higher temperature range and the change in temperature during oscillations was much greater. The unsheathed thermocouple wires produced oscillations at around 700 • C with a temperature change of only 7-8 • C [11]. In the experiments described here, the thermocouple wires were sheathed to within a few millimetres of the junction of the cobalt wire or foil and access to reaction gases was therefore greatly restricted.…”
Section: General Observation On the Oscillation Of Methane Oxidation mentioning
confidence: 99%
“…Our previous study showed that chromel-alumel thermocouples, when no other catalyst was present, can act as eective catalysts for the methane/oxygen reaction oscillating at temperatures between 700 and 740 8C, and nickel was identi®ed as the active catalyst [16]. In this paper we report on the further investigation into the oscillatory reaction kinetics over nickel foils during the reaction of oxidation of methane.…”
Section: Introductionmentioning
confidence: 90%